Appropriate evaluation of HIV prevention interventions: from experiment to full-scale implementation. (10th January 2007) - Hallett, Timothy B; White, Peter J; Garnett, Geoff P
Abstract : Background: Preventing HIV infection is still an essential goal in tackling the HIV/AIDS pandemic. Remarkably little is known about how best to reduce HIV incidence because most trials focus on the reduction of risk behaviours and assume an effect on HIV incidence. Objective: To discuss the evidence for the effectiveness of HIV prevention strategies, exploring the different types of evidence available: individual and community randomised controlled trials, and observational studies. Results: Although providing a gold standard for evidence, trials have been limited in their scope and are difficult to interpret and generalise. There have been examples of national level successes in preventing HIV which have been detected in surveillance data and understood through behavioural and modelling studies. These have the advantage of being to scale and indicating effectiveness rather than efficacy. Conclusions: Although randomised trials are important because of their scientific rigor, it is also important that evidence from observational epidemiology is not overlooked. Only if good quality, consistent data are available can the history of the HIV epidemic be appropriately analysed.